Association between video game addiction, stress, and bruxism in adolescents: a cross-sectional study - Ceylan Güzel; Fatma Dilek Erten; Ayda Seyidoğlu; Sümer Münevveroğlu (BMC Oral Health)
Abstract Background This study aims to examine the association between video game addiction stress levels, and both awake and sleep bruxism in adolescents. Given the increasing prevalence of digital addiction among young populations, understanding its potential impact on oral health is essential. Methods A cross-sectional study was conducted with 300 adolescents aged 10–19 years. Participants completed an online survey assessing video game addiction using the short form of the Digital Game Addiction Scale − 21 (DGAS-21), stress levels using the Perceived Stress Scale (PSS), and bruxism through self-reported questionnaires based on the American Academy of Sleep Medicine (AASM) criteria. Statistical analyses included chi-square tests, independent t-tests, and point-biserial correlation analysis. A significance level of p ≤ 0.05 was considered statistically significant. Results The prevalence of video game addiction in the sample was 50.3% (n = 151), with males significantly more affected than females (p < 0.05). Participants with video game addiction exhibited higher stress levels compared to non-addicted individuals (p < 0.001). A statistically significant association was found between video game addiction and both awake bruxism (r = 0.31, p < 0.001) and sleep bruxism (r = 0.28, p < 0.001). However, stress levels were not significantly correlated with bruxism (p > 0.05), suggesting that factors beyond stress may contribute to this relationship. Conclusion These findings indicate that video game addiction is associated with an increased likelihood of both awake and sleep bruxism in adolescents. However, the nature of this relationship remains unclear. Further longitudinal and experimental studies incorporating objective bruxism assessments are necessary to clarify potential causal mechanisms. Preventive measures focusing on digital well-being and stress management strategies should be considered in adolescent healthcare interventions.